Systematics and biogeography of the New Zealand sub-family Crambinae (Lepidoptera Pyralidae) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (Ph.D) in Zoology at Massey University, Palmerston North, New Zealand - Gaskin, David Edward (Massey University, 1968)
A few New Zealand Crambinae were described by Doubleday (1843), Walker (1863; 1864; 1866), Zeller (1863; 1877), Felder (1875) and Butler (1877). In this early work the same species were often described nearly simultaneously by as many as three authors, leading to much confusion in nomenclature. The first attempts at a systematic presentation of the New Zealand Crambinae. were made by Meyrick (1882 ; 1883; 1885; 1888), who also studied the Australian and Pacific Island Crambinae in the same period (1879; 1882a; 1886; 1897). His New Zealand studies culminated in the first revision of the group (1912a). In his descriptions, and in the revision, he relied almost entirely on the venation, forewing pattern and palpi structure for taxonomic characters. The great majority of the New Zealand Crambinae were grouped by Meyrick into the Palaearctic genus Crambus F. and the neotropical genus Diptychophora Zeller. He also erected an endemic genus Orocrambus (now attributed to Purdie, see later) to include a few alpine species. His type series were almost invariably specimens from the collections of G.V. Hudson in Wellington and R.W. Fereday in Christchurch. The first systematic examination of New Zealand Crambine genitalia was carried out by Philpott (1929), who figured 68 sets of genitalia. In this paper Philpott queried the validity of a few of Meyrick's species, but accepted his generic classification. Unfortunately the value of this paper (which deals with male genitalia only) to present day workers is much reduced by 10 name caption errors in the 68 figures. These are not merely spelling errors; several pairs of species names have become substituted, probably through errors in the original slide labelling. The confusion is compounded by two serious errors in his Crambus key. While basically a very valuable piece of work, Philpott's paper should not be used for Crambine male identification by anyone not fairly familiar with the genera concerned. However it can be used cautiously in conjunction with the very useful colour illustrations in Hudson's volumes (1928; 1939; 1951); as then some of the errors become obvious. During the last decade or so Bleszynski has revised the Palaeartic Crambinae (1965) and revised or begun to revise major genera in the Ethiopean Region (1964), the Old World tropics (1963b) and the Neotropical Region (1960a; 1966; 1967). A review of the world crambine genera and their types (1963a), and a catalogue of the known world species (Bleszynski and Collins, 1962) have also been very valuable contributions making the studies of regional workers, such as the present author, much easier. The overall classification of the Crambinae is still in some confusion. In the present work I have outlined and discussed what I think are the major characters dividing the subfamily above the generic level, and considered the relationships of this subfamily with the Scopariinae and Pyraustinae, an area of study where much more investigation and clarification is needed. All 80 known New Zealand species of Crambinae have been re-examined in the present study, and a preliminary re-examination and revision of 11 endemic Australian species has also been carried out. The latter study, although incomplete, has yielded valuable information concerning origins and relationships of the New Zealand Crambinae while the New Zealand studies have in turn suggested the line that a revision of the large and important Australian genus Hednota should take. My work has been made much easier by Dr. S. Bleszynski who has checked the types of the New Zealand Crambinae held in the British Natural History Museum collection and freely supplied me with his invaluable sketches of type genitalia; the efforts of Mr. P.E.S. Whalley and Mr. D. Carter of the Entomology Department, British Museum for listing type label data for me; Mr. I.F.B. Common of Entomology Division, CSIRO, Canberra, Mr. A. Neboiss of the National Museum of Victoria, Melbourne,and Mr. N. McFarland of the South Australian Museum, Adelaide who supplied me With valuable general information, label data and determined specimens for comparative study. A number of convenient abbreviations have been used in this work, and these are listed below.
Keywords: Crambinae; Moths; Lepidoptera; Snout moths; New Zealand moths